2011
DOI: 10.3109/01658107.2011.557760
|View full text |Cite
|
Sign up to set email alerts
|

Stratus OCT Quality Control in Two Multi-Centre Multiple Sclerosis Clinical Trials

Abstract: The University of California (UC) Davis Reading Center evaluated 19,961 scans from 981 subjects in two multiple sclerosis therapeutic trials with the aim of determining the influence of optical coherence tomography quality control procedures on error rates. There was no optical coherence tomography technician certification in Trial 1, and technicians had very limited monitoring and feedback during the trial in view of the fact that data were received retrospectively. However, technicians were certified in Tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…21 The success of this study, which used 24 sites naïve to SD-OCT data collection, shows the utility of an OCTRC. [22][23][24][25][26][27] Interocular correlations for all SD-OCT parameters reflecting papilledema-related swelling in the ONH or peripapillary retina were highly significant. The OCT continuous variable measures showed that most IIH patients, with newly diagnosed disease and mild visual field loss (PMD range, À2.00 to À7.00 dB), have relatively symmetrical amounts of papilledema.…”
Section: Discussionmentioning
confidence: 92%
“…21 The success of this study, which used 24 sites naïve to SD-OCT data collection, shows the utility of an OCTRC. [22][23][24][25][26][27] Interocular correlations for all SD-OCT parameters reflecting papilledema-related swelling in the ONH or peripapillary retina were highly significant. The OCT continuous variable measures showed that most IIH patients, with newly diagnosed disease and mild visual field loss (PMD range, À2.00 to À7.00 dB), have relatively symmetrical amounts of papilledema.…”
Section: Discussionmentioning
confidence: 92%
“…The OCT Reading Center received 18,733 scans from 939 patients at 96 sites. From this database, 2,880 high-quality representative OCT scans determined by the above strict quality control criteria (24) were selected. Only patients with complete data of each eye’s macula and RNFL were used, representing 1,434 eyes in 717 patients.…”
Section: Resultsmentioning
confidence: 99%
“…As published previously, scans were excluded from the final database if they met any of the following criteria: signal strength less than 7 (except in the case of a few clearly visible fovea or optic nerve scans with correct centration), exported data missing, extra scans, decentered scans, wrong scans or scanner used, or they required redraw by the technician due to segmentation artifact (24). …”
Section: Methodsmentioning
confidence: 99%
“…Longitudinal studies of OCT underscore the value of a central OCT reading centre for clinical trials ( Keltner et al , 2011 ). Analogous to a central MRI reading centre, which has become the standard approach in multiple sclerosis trials, a central OCT reading centre would be responsible for training sites in standardized image acquisition procedures, developing case report forms, and deploying computerized retinal segmentation software.…”
Section: Visual Outcomes In Optic Neuritis and Multiple Sclerosis CLImentioning
confidence: 99%